PERSEPSI KELUARGA PELAKU BUNUH DIRI TENTANG STIGMA SOSIAL DI GUNUNGKIDUL - Sungkana, Mayantoni; Sutejo (MEDIA ILMU KESEHATAN, 2012)
Background: Factors associated with suicidal behavior are the inability to communicate one’s needs and feelings. Public perception of suicide is influenced by culture. The stigma of society will affect families committing suicide. Social stigma often leads to exclusion of a person or group as a result of a lack of social support from those around the person. The area with the highest rates of suicide in Indonesia is Gunungkidul District, noted that in 2011 there were 30 suicidal cases. Objective: To determine the perception of the suicide victim's family about the social stigma in Gunungkidul District. Methods: This was a qualitative study, with a descriptive exploratory case study design. Data collection was with in-depth interviews conducted at 3 informants. The criteria to become informants were as follows: the closest person and living at home with the suicide, at least 18 years of age, sound mind and not mentally ill, and able to communicate orally. Data validation was by triangulation to relatives, close neighbors and village heads. Results: The qualitative result showed that the family of the suicide received the judgment given by the society. Family made suicide on family members as a means for self introspection. Society was consciously trying to keep the family feeling of committing suicide and providing support for the family from the tragedy experienced. Conclusion: The family of the suicide did not feel the negative stigma from society. There is a need of early identification of mental health problems in the family or society and preventive efforts to provide health education to the society. Keywords: Social stigma, family, suicide